Enhancing students' digital literacy through digital-based classroom management in informatics learning - Devi Sylvianica; Sudarwan Danim; Azizatul Khairi (Indonesian Journal of Educational Development (IJED), 2026)
This study examines digital-based classroom management to enhance students' digital literacy in Informatics learning. The rapid expansion of educational technology requires structured classroom strategies that systematically foster multidimensional digital competencies rather than merely support content delivery. This research aims to analyze how digital-based classroom management through the 1 Cerdas Application enhances students' digital literacy competencies. A descriptive qualitative approach was employed in a public lower secondary school involving school leaders, Informatics teachers, and students selected purposively. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using an interactive qualitative model consisting of data condensation, data display, and conclusion drawing. The findings indicate that structured platform-based management improved students' technical proficiency, collaborative engagement, creative digital production, information evaluation skills, and ethical technology awareness, although infrastructure instability and varied digital readiness remained challenges. The study concludes that digital-based classroom management serves as a systemic pedagogical strategy for strengthening digital literacy and recommends continuous infrastructure improvements and teacher professional development to sustain the effectiveness of innovation.